SYNTHESIS AND ANALYSIS OF ZINC METHIONINE, ZINC GLYCINE, COPPER LEUCINE, AND COPPER GLYCINE COMPLEXES USING ATOMIC ABSORPTION SPECTROPHOTOMETRY - Nastiti, Sekar Alinda; ., Harmita; Jatmika, Catur (International Journal of Applied Pharmaceutics, 2018)
Objective: The aim of this study was to perform metal-amino acid synthesis and to analyze the free and bonded mineral concentrations. Methods: In this study, the synthesis of amino acid metal complexes was carried out by reacting free metal ions, derived from a water-soluble metal salt, with amino acids in a 1:2 molar ratio. Results: The respective yields of this synthesis process were 95.38%, 95.95%, 76.31%, and 93.91% for zinc (Zn)-methionine (Zn(Met)2), Zn-glycine (Zn(gli)2), copper-leucine (Cu(leu)2), and Cu-glycine (Cu(gli)2) complexes, respectively. The metal-amino acid complexes were then separated using column chromatography and further analyzed by atomic absorption spectrophotometry (AAS). The bonded metal concentrations of the Zn(Met)2, Zn(gli)2, Cu(leu)2, and Cu(gli)2 complexes were 189.32 mg/g, 353.78 mg/g, 180.89 mg/g, and 275.11 mg/g, respectively. The free metal concentrations of the Zn(Met)2, Zn(gli)2, Cu(leu)2, and Cu(gli)2 complexes were 13.57 mg/g, 12.92 mg/g, 0.19 mg/g, and 2.12 mg/g, respectively. Conclusion: In this study, Zn(Met)2, Zn(gli)2, Cu(leu)2, and Cu(gli)2 complexes were successfully formed and analyzed. The mineral concentration in each complex differed depending on the type of mineral and ligand.